Beauty Standards In Film Imperfect (2019) - Siska Nur Setyarani; Jeyta Kistina Lubis; Niken Nurdiyanti; Muhammad Khalil Nurhadianah Putra; Febryantoro Mali Leto (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study examines beauty standards and their social impacts on women as represented in the film Imperfect (2019). In social life, beauty standards often place women under specific physical judgments, such as slim body shape, skin color, and outward appearance, which subsequently influence social acceptance and self-confidence. This research aims to reveal how beauty standards are constructed in the film and how they affect the main character’s self-identity and social relationships. The study employs a qualitative approach using discourse analysis. The data consist of dialogues, scenes, and visual elements that represent physical judgment, body shaming, and social pressure related to beauty standards. Data were collected through film observation and documentation and analyzed descriptively. The findings indicate that Imperfect portrays beauty standards as a form of social pressure that leads to discrimination, bullying, and unequal treatment of women in both family and workplace settings. The film also illustrates the main character’s process of self-awareness in rejecting narrow beauty ideals and developing self-acceptance. Therefore, Imperfect serves as a form of social criticism that highlights the negative impacts of dominant beauty ideals and emphasizes the importance of appreciating bodily diversity and female identity.